Critique of religious thought - ʻAẓm, Ṣādiq Jalāl (Gerlach Press, 2015)
Sadik al-Azm's 'Critique of Religious Thought' set off one of the great Arab intellectual uproars of the twentieth century, leading to the author's imprisonment and trial for mocking religion and inciting sectarian conflict. As in his earlier 'Self-Criticism after the Defeat', al-Azm takes on the taboos of the age and their sponsors: the religious elites. In this book he attempts to awaken the Arab mind from its dogmatic slumber, leading it out of the Middle Ages and into a modern world characterized by science and rationality.